التحقيق التأديبي كضمانة لحماية الموظف العام - خرباشي محمد -خير عبد الباسط (جامعة المسيلة, 2024)
The subject of the memorandum addresses the disciplinary investigation as a guarantee for the public employee within the framework of the Public Service Law, which is Order No. (06/03), with the aim of reaching complete knowledge about this subject, its legal procedures, as well as the powers of the authority that has the power to appoint, and the Disciplinary Committee. The descriptive approach was adopted in this study. Analytical analysis 'to find out how the legislator organized and controlled their investigative powers' and among the results of this study is that the disciplinary investigation must be based on the foundations regulated by the legislator such as writing, reasoning, neutrality and objectivity 'as well as adherence to the time period in order to avoid causing harm to the public interest and the public employee'. The legislator stressed the necessity of respecting the procedures until... Do not be subject to invalidation
Keywords: Disciplinary investigation - Guarantees– Protection - Protection- Precautionary measures - Precautionary suspension